Influence of Electronic Trust, Satisfaction, and Engagement on Consumption Behavior in Mobile Legends Players - Indra Eka Wardana Toii; Nur Mila Sari; Xenia Irene Sandy Landjang; Alfani Laura Harikedua (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid rise of electronic sports, particularly Mobile Legends: Bang Bang, has reshaped digital consumption behavior in regional areas like Jayapura City. This study investigates the influence of electronic trust, electronic satisfaction, and consumer electronic sport engagement on electronic consumption behavior among Mobile Legends players. Using a quantitative causal research design, data were collected from 150 active players aged 18 years or older in Jayapura through purposeful sampling. An online questionnaire with a five-point Likert scale was distributed via WhatsApp, and data were analyzed using SmartPLS software to evaluate direct relationships. The results show that electronic trust significantly enhances electronic satisfaction, which in turn drives consumer electronic sport engagement and electronic consumption behavior. Consumer electronic sport engagement also directly influences electronic consumption behavior. However, electronic trust does not directly affect engagement or consumption. These findings highlight the critical roles of satisfaction and engagement in encouraging digital purchases in electronic sports. Game developers and local organizers in Jayapura should enhance platform usability and host community events to boost satisfaction and engagement, thereby fostering greater consumption among players in regional markets.